Análisis de la gestión del agua en comunidades rurales de Zamora, Michoacán, México - López Chacón, Renné Ibeth (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
Integrated Water Resources Management (IWRM) was defined by the Technical Committee of the World Water Partnership (GWP) as "A process that promotes the coordinated management and development of water, soil and other related resources, with the to maximize economic results and social welfare in an equitable manner without compromising the sustainability of vital ecosystems " For years, several important factors have been minimized in decision-making in watershed management, where the role of social participation and resource planning have not figured much. It is important to contemplate these elements in order to properly manage the water resources available for the following generations. In rural communities of our country, this task has been difficult due to political, economic, social, cultural, spatial factors, etc. In the selected communities there is no diagnosis of their sources of water supply. In this context, it is important to determine the current state of the water in the localities and know their management form. The water crisis is linked to the reduction of the availability of drinking water, in quality and quantity, and with the environmental problems associated with the use of water, which are facing different areas of the planet. One of the environmental problems related to the reduction of water resources available for human use and consumption is pollution, where its physical, chemical or microbiological components are found in concentrations such that their effect is toxic or limiting to the life of other organisms. A diagnosis was made of the state of the water resources of the communities of La Rinconada, San Esteban, Cerrito de Catipuato and La Labor, which included a questionnaire applied to the residents.

La Gestión Integrada de Recursos Hídricos (GIRH) fue definida por el Comité Técnico de la Asociación Mundial para el Agua (GWP) como "Un proceso que promueve la gestión y el desarrollo coordinados del agua, el suelo y los otros recursos relacionados, con el fin de maximizar los resultados económicos y el bienestar social de forma equitativa sin comprometer la sostenibilidad de los ecosistemas vitales”. Durante años, se han minimizado diversos factores de importancia en la toma de decisiones de la gestión de cuencas, donde el papel de la participación social y la planificación del recurso han figurado poco. Es importante contemplar estos elementos para gestionar adecuadamente el recurso hídrico disponible para las siguientes generaciones. En las comunidades rurales de nuestro país, ha resultado difícil esta tarea debido a factores políticos, económicos, sociales, culturales, espaciales, etc. En las comunidades seleccionadas no hay un diagnóstico de sus fuentes de abastecimiento de agua. En este contexto, es importante determinar el estado actual del agua en las localidades y conocer su forma de gestión. La crisis del agua se vincula con la reducción de la disponibilidad de agua potable, en cantidad y en calidad adecuadas, y con los problemas ambientales asociados al uso del agua, que están afrontando diversas zonas del planeta. Uno de los problemas ambientales relacionados a la disminución del recurso hídrico disponible para uso y consumo humano es la contaminación, donde sus componentes físicos, químicos o microbiológicos se encuentran en concentraciones tales que su efecto es tóxico o limitante para la vida de otros organismos. Se realizó un diagnóstico del estado de los recursos hídricos de las comunidades de La Rinconada, San Esteban, Cerrito de Catipuato y La Labor, que incluyó un cuestionario aplicado a los pobladores.
Instituto de Investigaciones en Ciencias de la Tierra. Maestría en Geociencias y Planificación del Territorio
Keywords: info:eu-repo/classification/cti/1; INICIT-M-2018-1134; Gestión hídrica integrada; Comités rurales; Agua subterránea; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4411